Sodium Orthovanadate Effect on Outflow Facility and Intraocular Pressure in Live Monkeys - Tan, James C.H. (2010)
Sodium orthovanadate (Na(3)VO(4)) is reported to reduce IOP by affecting aqueous formation, but whether it also affects outflow facility (OF) is unclear. We tested the effect of Na(3)VO(4) on OF and intraocular pressure (IOP) in live cynomolgus monkeys, and on actin and cell adhesion organization in cultured human trabecular meshwork (HTM) cells. Total OF (n = 12) was measured by 2-level constant pressure perfusion of the monkey anterior chamber (AC) before and after exchange with 1 mM Na(3)VO(4) or vehicle in opposite eyes. Topical 1% Na(3)VO(4) or vehicle only was given twice daily (each 2×20 μL drops) for 4 days to opposite eyes (n = 8), and Goldmann IOP was measured before and hourly after treatment for 6 hours on Days 1 and 4. Filamentous actin and vinculin-containing cell adhesions were examined by epifluorescence microscopy after the cells had been incubated with 1 mM Na(3)VO(4) for 24 hours. A) In monkeys, Na(3)VO(4) increased OF by 29.3 ± 8.8% (mean ± s.e.m.) over the perfusion interval when adjusted for baseline and contralateral eye washout (p = 0.01; n = 12). B) Day 1 baseline IOP was 16.2 ± 1.5 mmHg in treated eyes and 15.9 ± 1.3 mmHg in the contralateral control eyes. Following treatment on Day 1, IOP was no different (p>0.05) between treated eyes and control eyes at any time-point or compared to baseline. Day 4 mean IOP averaged over hours 2–6 was 13.5 ± 0.8 mmHg in treated eyes and 16.1 ± 0.2 mmHg in control eyes. Treated eye IOP was lower than its Day 4 baseline (p<0.005), lower than control eyes for the same Day 4 interval (p = 0.009), and lower than the Day 1 baseline (p = 0.0000). Control eye IOP on Day 4 was not significantly different from baseline on Day 1. C) Incubation of HTM cells with 1 mM Na(3)VO(4) for 24 hours caused a loss of actin stress fibers and vinculin-containing adhesions. Cell retraction and separation was also observed in vanadate-treated cultures. Reformation of actin stress fibers, vinculin-containing adhesions and confluent monolayers occurred within 24 hours after Na(3)VO(4)-containing culture medium was replaced with Na(3)VO(4)-free medium. Ocular administration of Na(3)VO(4) to live monkeys significantly increases OF and reduces IOP. Na(3)VO(4) reversibly disrupts actin and cell adhesion organization and causes retraction and separation of cultured HTM cells. Na(3)VO(4) increases pressure-dependent outflow in live monkeys. Altered actin architecture in the TM may play a part in this increased OF.